Antibacterial and antioxidant activities of the seeds of artocarpus heterophyllus / Eumi Nazera Mohd Nazir - Mohd Nazir, Eumi Nazera (2017)
The Jackfruit tree, which also known as Artocarpus heterophyllus, is widespread tree all over Asia. The seed of fruit from this species was studied. The seed was extracted using soxhlet extractor with hexane, dichloromethane (DCM) and methanol. The extraction yield obtained were 1.9%, 2.6% and 2.3% of extract methanol, DCM and hexane respectively. Thin Layer Chromatography (TLC) analysis displayed a suitable solvent system to separate the component within each extract. The identified solvent system suitable for methanol extract was DCM:chloroform:hexane (3:2:2), for DCM extract, the identified solvent system was chloroform: hexane (2:1), while, for hexane extract, the identified solvent system was toluene:ethyl acetate:formic acid (7:1:1). The crude extracts was then undergone several test which was antioxidant and antibacterial. The antioxidant test was done using DPPH Radical Scavenging Activity method and the antibacterial test was done using Disc Diffusion method. It was found that all sample extracts had a low antioxidant activity with the percentage radical scavenging activity lower than 22% compared to ascorbic acid. For the antibacterial test, methanol extract exhibited a highest inhibition zone of 16 mm against Salmonella sp., 14 mm against E.coli, and, 18 mm against B.subtillis and S. aureus.